Quality and Efficiency: Incompatible Elements in Translation Practice? - Ørsted, Jeannette (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractThe aim of this article is to describe the quality assessment procedures in a large, national translation company. The company is more than ten years old, but the past five years' growth rates have been rapidly increasing. The growth in turnover can be attributed both to a high degree of customer loyalty based on a high level of efficiency and trust, and on high, well-defined and transparent quality standards. The company is based on the idea that translators should function in a working environment based on full-term employment. Consequently the increase in turnover has involved recruiting a large number of translators and support services in the IT-department. This is why quality assessment procedures are no longer an individual responsibility, but have become a corporate issue. Quality procedures must therefore be part of the daily routines and involve all aspects of the business. To understand the conditions of the translation market today, the author provides an overview of the market based on the ASSIM-study and information on the new economy. After that she presents the case of Translation House of Scandinavia and finally she discusses some of the possible quality assurance systems that are available today and are used by the translation industry.